From Bystanders to Upstanders: Cultivating Digital Citizenship to Combat Cyberbullying among Vocational Students High School Students - Susanto, Rofian Dedi; Lindawati, Sri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2026)
The penetration of digital technology has heavily disrupted adolescent interaction patterns. The pervasive use of social media, when lacking adequate moral literacy, triggers the normalization of cyberbullying within school environments. This community service initiative aimed to fortify students' digital communication ethics and cognitive empathy through a novel framework: the Upstander-Based Digital Ethics Intervention. Involving 39 twelfth-grade students from SMK Kesuma Bangsa 2 Depok, the intervention utilized a Participatory Communication Approach. The program's stages encompassed baseline mapping, interactive digital citizenship education, case study analysis, role-playing simulations, and comprehensive evaluations. Quantitative outcomes revealed a substantial cognitive transformation, with the average literacy score surging by 60% (from 55 to 88). Psychomotor evaluations via role-play demonstrated that students successfully exercised assertive communication, shifting their behavioral tendencies from passive spectators (bystanders) to active defenders (upstanders). The findings were scrutinized using social learning and behavior change theories. Despite the potential for short-term observational bias, this program successfully laid the groundwork for a healthy cyber ecosystem through collective ethical commitments and the provision of a sustainable educational module to the institution.